Co-Designing Urban Carbon Sink Parks: Case Carbon Lane in Helsinki - Tammeorg, Priit; Soronen, Päivi; Riikonen, Anu; Salo, Esko; Tikka, Suvi; Koivunen, Minja; Salonen, Anna-Reetta; Kopakkala, Topi; Jalas, Mikko (Frontiers in Environmental Science, 2021)
In order to achieve the goals of carbon (C) neutrality within next 20 year, municipalities worldwide need to increasingly apply negative emission technologies. We focus on the main principles of urban demonstration areas using biochars for C sequestration and explore the lessons learned from a co-creation process of one such park, Hyväntoivonpuisto in Helsinki, Finland. Demonstration sites of urban C sinks in public parks must be safe, visible and scientifically sound for reliable and cost-effective verification of carbon sequestration. We find that different interests can be arbitrated and that synergy that emerges from co-creation of urban C sink parks between stakeholders (scientists, city officials, companies and citizens) can result in demo areas with maximized potential for impact, dissemination and consideration of principles of scientific experimentation.